PENGARUH RISIKO GEOPOLITIK, KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN INDUSTRI PERBANKAN PERIODE 2020-2024 - Gladies Lydia Mariana Tombokan; Ivonne Saerang; Joy Tulung (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
ABSTRACT:  The banking industry plays a strategic role in the capital market because it reflects the stability of the financial sector and is an important indicator of national economic conditions. This study aims to analyze the influence of geopolitical risk, institutional ownership, and company size on the financial performance of the banking industry in the 2020–2024 period. The research data uses annual panel data with a sample of 47 companies as the cross-section dimension and the 2020–2024 period as the time series dimension. The sampling technique was purposive sampling with the criteria of companies being listed and actively traded, having complete financial reports, and being considered fairly healthy with ROA ≥ 0.5%, resulting in a total of 28 observations. The research method uses a quantitative approach with panel data regression analysis. The results show that geopolitical risk, institutional ownership, and company size simultaneously influence the financial performance of the banking industry. Partially, company size has a positive and significant effect on company performance, while geopolitical risk and institutional ownership have a negative and insignificant effect on company performance in the banking industry.